Helpful and challenging aspects of breastfeeding in public for women living in Australia, Ireland and Sweden: A cross-sectional study - Hauck, Yvonne; Kuliukas, Lesley; Gallagher, L.; Brady, V.; Dykes, C.; Rubertsson, C. (BMC, 2020)
Background: Breastfeeding in public continues to be contentious with qualitative evidence confirming that women face many challenges. It is therefore important to gain understanding of not only the challenges but also what women perceive is helpful to breastfeed in public.